Construction of Pseudomonas aeruginosa SDK-6 with synthetic lipase gene cassette and optimization of different parameters using response surface methodology for over-expression of recombinant lipase - Kaur, Damanjeet; Singh, Rupinder Pal; Gupta, Saurabh (Folia microbiologica, 2024)
Lipases are industrially important enzymes having vast applications in various fields. Cloning and expression of lipase enzyme-encoding genes in suitable host lead to their widespread use in different fields. The present study represents the first attempt towards the expression of the synthetic lipase gene in Pseudomonas aeruginosa. An alkalophilic lipase gene (GenBank accession number: NP_388152) from Bacillus subtilis was synthetically designed and introduced in the pJN105 vector and subsequently cloned in Pseudomonas aeruginosa SDK-6. Agarose gel electrophoresis confirmed the transformation of SDK-6, exhibiting a band difference of ~ 700 bp between native and recombinant pJN105. Further amplification of cloned lipase gene was confirmed using PCR amplification with Lip 1 and Lip 2 primers respectively, followed by restriction analysis. Approximately 15-fold increase in lipase production was observed in recombinant Pseudomonas as compared to the native strain. One factor at a time (OFAT) analysis revealed L-arabinose, inoculum size (0.5%; v/v), and agitation (120 rpm) as significant factors affecting the over-expression of lipase enzyme. Optimization of enzyme induction conditions by central composite design (CCD) led to 1.60-fold increase in the production of lipase at 0.65% (w/v) inducer concentration, OD600-1.075 before induction and 35 °C post induction temperature with overall lipase production of 50.50 IU/mL. Statistical validation of observed value via ANOVA showed an F-value of 138.70 at p < 0.01 with R2 of 0.9921.
Keywords: genetické vektory; Arabinose; Lipase; Bacillus subtilis; lipasa; Genetic Vectors; Pseudomonas aeruginosa; Cloning, Molecular; Bacterial Proteins; Recombinant Proteins; klonování DNA; exprese genu; Gene Expression; rekombinantní proteiny; arabinosa; bakteriální proteiny